Dissociated coupling between cerebral oxygen metabolism and perfusion in the prefrontal cortex during exercise: a NIRS study - Hiura, Mikio; Funaki, Akio; Shibutani, Hirohide; Takahashi, Katsumi; Katayama, Yoichi (Frontiers in Physiology, 2023)
The present study used near-infrared spectroscopy to investigate the relationships between cerebral oxygen metabolism and perfusion in the prefrontal cortex (PFC) during exercises of different intensities.Methods: Twelve recreationally active men (age, 24 ± 6 years) were enrolled. They performed 17 min of low-intensity exercise (ExL) followed by 3 min of moderate-intensity exercise (ExM) at constant loads. Exercise intensities for ExL and ExM corresponded to 30% and 45% of the participants' heart rate reserve, respectively. Cardiovascular and respiratory parameters were measured. We used near-infrared time-resolved spectroscopy (TRS) to measure the cerebral haemoglobin oxygen saturation (ScO2) and total haemoglobin concentration ([HbT]), which can indicate cerebral blood volume (CBV). As the cerebral metabolic rate for oxygen (CMRO2) is calculated using cerebral blood flow (CBF) and ScO2, we assumed a constant power law relationship between CBF and CBV based on investigations using positron emission tomography. We estimated the relative changes in CMRO2 (rCMRO2) and CBV (rCBV) from the baseline. During ExL and ExM, the rate of perceived exertion was monitored and alterations in the subjects' mood induced by exercise were evaluated using the Profile of Moods Scale-Brief.Results: Three min after exercise initiation, ScO2 decreased and rCMRO2 surpassed rCBV in the left PFC. When ExL changed to ExM, cardiovascular variables and the sense of effort increased concomitantly with an increase in [HbT], but not in ScO2, and the relationship between rCMRO2Exercise-induced metabolic changes in brain 2 and rCBV was dissociated in both sides of the PFC. Immediately after ExM, [HbT] and ScO2 increased and the disassociation between rCMRO2 and rCBV was prominent in both sides of the PFC. While blood pressure decreased and a negative mood state was less prominent following ExM compared with that at rest, ScO2 decreased at 15 min after exercise and rCMRO2 surpassed rCBV in the left PFC.Dissociated coupling between cerebral oxidative metabolism and perfusion in the PFC was consistent with the effort required for increased exercise intensity and associated with post-exercise hypotension and altered mood status after exercise. Our result demonstrates the first preliminary results dealing with the coupling between cerebral oxidative metabolism and perfusion in the PFC using TRS.